Occult Dirofilariosis in Dogs of North Eastern Region in India - Sonjoy Kumar-Borthakur; Dilip Kumar-Deka; Saidul Islam; Prabhat Chandra-Sarmah (Tehran University of Medical Sciences, 2016)
Background: The North Eastern Region in India is endemic for canine heartworm disease but in clinics accurate diagnosis is some times difficult. The aim of the present study was to determine the prevalence of occult infections for heartworm disease in canine in two geographical regions of North Eastern India. Methods: A total of 782 numbers of three categories of dogs namely, working dogs of military and paramilitary forces, pet dogs and stray dogs were screened for the presence of heartworm infection from August 2011 to July, 2012 in Guwahati (Assam) and Aizawl (Mizoram). Conventional, immunological and molecular techniques were followed for this epidemiological study. The criteria to determine the occult heartworm cases were based on the differences between heartworm positive cases in PCR test and antigen ELISA test. Results: The findings revealed an overall 22.69 percent occult case. The working dogs had highest prevalence (60%) followed by pet (29.16%) and stray dogs (17.75%). Conclusion: The highest percentage of occult heartworm infection was present in working dogs maintained under military or paramilitary forces.